2011
DOI: 10.1371/journal.pone.0022429
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Specific Fluorescent Probes for Functional Analysis of the Three Major Types of Mammalian ABC Transporters

Abstract: An underlying mechanism for multi drug resistance (MDR) is up-regulation of the transmembrane ATP-binding cassette (ABC) transporter proteins. ABC transporters also determine the general fate and effect of pharmaceutical agents in the body. The three major types of ABC transporters are MDR1 (P-gp, P-glycoprotein, ABCB1), MRP1/2 (ABCC1/2) and BCRP/MXR (ABCG2) proteins. Flow cytometry (FCM) allows determination of the functional expression levels of ABC transporters in live cells, but most dyes used as indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 33 publications
0
93
0
Order By: Relevance
“…Furthermore, AZX revealed the capacity to inhibit cell proliferation in a concentrationdependent manner in HepG2 cells within 24 h, while most of the cell lines showed the same result only after 48 h. A549 and VSa16 cell lines are likely to need more than 48 h for AZX to pass through the cellular membrane as they both showed low r 2 , with A549 not even fitting the regression model used with 24 h data. On the other hand, most carcinoma cells develop mechanisms of multidrug resistance, based on the existence of transporter proteins (e.g., MDR1, MRP1/2, BCRP/MXR), and the human lung adenocarcinoma epithelial cell line A549 is considered a multidrug resistance cell line expressing MRP1 and BCRP proteins (Lebedeva et al, 2011). The comparison of the six IC 50 results revealed that the H9c2 cell line is more sensitive to AZX than the others, since it showed cytotoxicity at smaller concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AZX revealed the capacity to inhibit cell proliferation in a concentrationdependent manner in HepG2 cells within 24 h, while most of the cell lines showed the same result only after 48 h. A549 and VSa16 cell lines are likely to need more than 48 h for AZX to pass through the cellular membrane as they both showed low r 2 , with A549 not even fitting the regression model used with 24 h data. On the other hand, most carcinoma cells develop mechanisms of multidrug resistance, based on the existence of transporter proteins (e.g., MDR1, MRP1/2, BCRP/MXR), and the human lung adenocarcinoma epithelial cell line A549 is considered a multidrug resistance cell line expressing MRP1 and BCRP proteins (Lebedeva et al, 2011). The comparison of the six IC 50 results revealed that the H9c2 cell line is more sensitive to AZX than the others, since it showed cytotoxicity at smaller concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Medium used for this experiment was opti-MEM and each solution was prepared in buffer at pH of 7.4, and fluorescence readings were performed using Infinite 200 PRO multimode plate reader (Tecan) with excitation and emission wavelengths of 492 and 518 nm, respectively. Efflux activity was calculated using formula: % Efflux activity = 100*((FI inh − FI 0 )/FI inh ), wherein FI inh and FI 0 are the fluorescence intensity values measured in the presence and absence of inhibitor (29). Fluorescence intensities were normalized with total protein content.…”
Section: Carboxyfluorescein Diacetate Efflux Assaymentioning
confidence: 99%
“…CMFDA is a non-fluorescent lipophilic compound which is cleaved by intracellular esterases then modified to generate a hydrophilic membrane impermeant fluorescent product, GSMF, within the cells. GSMF is a specific substrate for MRP/Mrp isoforms (Forster et al, 2008;Lebedeva et al, 2011Lebedeva et al, 2011. SH-SY5Y or N2a cells were exposed to a range of concentrations of CMFDA (0-1.5 mM) and intracellular fluorescence was measured in the absence and presence of MK571 (10 mM), a specific inhibitor of MRP/Mrp isoforms (Luders et al, 2009).…”
Section: Demonstration Of the Expression Of Mrp/mrp Isoforms In Humanmentioning
confidence: 99%